Les apports de l’économie institutionnelle à l’analyse des dispositifs de paiements pour services environnementaux : État des lieux et perspectives - Colas Chervier; Sarah Millet-Amrani; Philippe Méral (Développement Durable et Territoires)
This paper gives an overview of the contribution of institutional economics to the analysis of payments for environmental services (PES) in the recent scientific literature. This work is based on the review of a selection of papers that appeared to us as the most significant dealing with this topic. Three main analytical themes were identified : the conceptualization of PSE, architecture and governance of PES mechanisms and the understanding of their impact. Our analysis shows that different theoretical approaches from institutional economics coexist, sometimes within the same analytical framework. This leads us to discuss the complementarities and potential contradictions inherent to the epistemological pluralism.